Adaptive distributed observer and the cooperative control of multi-agent systems. Issue 1 (2nd January 2017) - Huang, Jie
Abstract : The distributed observer approach has been an effective way to synthesise a distributed control law for a multi-agent system. However, this approach assumes that all the followers know the system matrix of the leader system, and this assumption may not be desirable in some applications. In this note, we will further introduce an adaptive distributed observer, which is able to estimate both the state and the system matrix of the leader and thus does not require that all the followers know the system matrix of the leader system. We will also point out some applications of the adaptive distributed observer to several cooperative control problems of multi-agent systems such as the leader-following consensus problem, the cooperative output regulation problem and rendezvous and/or flocking.